2016
DOI: 10.14569/ijacsa.2016.070716
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating Web Accessibility Metrics for Jordanian Universities

Abstract: Abstract-University web portals are considered one of the main access gateways for universities. Typically, they have a large candidate audience among the current students, employees, and faculty members aside from previous and future students, employees, and faculty members. Web accessibility is the concept of providing web content universal access to different machines and people with different ages, skills, education levels, and abilities. Several web accessibility metrics have been proposed in previous yea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
2
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 23 publications
(27 reference statements)
0
2
0
Order By: Relevance
“…Similar studies have also been conducted to evaluate the accessibility of government websites in Bangladesh [11], Dubai [12], India [13] [14], Saudi Arabia [15] [16], Turkey [17], Kyrgyz Republic [18], Malaysia [19], and the United States [20]. Also in these studies [21] [22][23] [24] [25], they evaluated the accessibility of education websites. Khan, et al [26] conducted another study manually by using WCAG 2.0.…”
Section: Introductionmentioning
confidence: 99%
“…Similar studies have also been conducted to evaluate the accessibility of government websites in Bangladesh [11], Dubai [12], India [13] [14], Saudi Arabia [15] [16], Turkey [17], Kyrgyz Republic [18], Malaysia [19], and the United States [20]. Also in these studies [21] [22][23] [24] [25], they evaluated the accessibility of education websites. Khan, et al [26] conducted another study manually by using WCAG 2.0.…”
Section: Introductionmentioning
confidence: 99%
“…With the growing number of users (including traditionally marginalized groups such as people with disabilities) interacting the web over time, the increased adequacy of web accessibility has become more relevant as to represent all of them [2]. "Web accessibility is the concept of providing web content that is universally accessible to different machines and people with different ages, skills, education levels, and abilities" [3]. However, the prevalence of web accessibility is found to be lacking when it comes to countries in Africa [4], where around 40 percent of the total population suffers from sort of disability, according to the World Health Organization (WHO) [5].…”
Section: Introductionmentioning
confidence: 99%
“…The National Institute of Statistics of Mozambique, INE is also responsible for census reporting [6]. Sida [6], have argued that INE lacks specific instructions and funding to collect information regarding disability and the different studies results reflect the absence of a commonly agreed definition 3 of disability and poor data collection methods. Sida is a government agency working on behalf of the Swedish Parliament and Government to reduce poverty in the world [6].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Bearing in mind that older people are considered one of the main groups at risk in this pandemic, it is especially important that they are the ones who have the most access to the content offered by information sources such as the WHO [ 9 ]. From the point of view of web accessibility, it should be emphasised how few studies have been carried out on international and official organisations with important social responsibilities such as the WHO, as they are more oriented towards the education sector such as universities and local corporations such as town councils [ 10 , 11 , 12 , 13 , 14 ]. Most of these studies do not focus on recent recommendations but only on some that have been detected in the area of education [ 15 , 16 ]; likewise, studies have shown that citizens’ dependence on the media is more intense in crisis situations [ 17 ].…”
Section: Introductionmentioning
confidence: 99%